Genetic Variability among different populations of Grewia optiva Drummond in low and mid hill zones of Himachal Pradesh. - Sankhyan, H.P.; Dhiman, Jyoti; Rana, Neerja; Chand, Krishan (Indian Journal of Agroforestry, 2023)
The study was conducted to estimate genetic variability among different populations of Grewia optiva Drummond under field conditions of Himachal Pradesh, India. Seed source (S8) Barthi exhibited outstanding performance for growth parameters. Based on the progeny performance, genotypes S1G1 (Uncha-gaon), S2G3 (Gaddo), S3G2 (Jajjar), S5G2 (Bala) and S6G3 (Jinzkari) were found to be most promising for growth traits. The percentage of genotypic coefficient of variance (GCV) and phenotypic coefficient of variation (PCV) was recorded maximum for branch angle i.e., 40.56% and 40.65 %, respectively. Percentage of phenotypic coefficient of variation observed higher than genotypic coefficient of variations for all the traits. Highly significant and positive genotypic and phenotypic correlation was observed in plant height with number of branches (rg=0.324, rp=0.317) and leaf area with basal diameter (rg=0.326, rp=.307). High heritability was reported for all growth traits. The highest genetic gain was recorded for branch angle (54.74) and moderate for leaf area (29.95. The highest genetic advance (54.74) reported in branch angle. Genotypes were clustered into two distinct groups using hierarchical clustering analysis. The maximum inter- cluster distance was observed between S2G3 and S7G2, whereas, the maximum intra-cluster distance was observed between S2G3 and S8G3 in cluster I and S1G1 and S7G2 in cluster II. Principal components (PCI-PCIV) cumulatively accounted for 76.31 % of total variation. The PCA I explained 23.18 % of the total variance, associated with plant height, branch angle, basal diameter.